Synergistic catalysis of species in molten salt hydrate for conversion of cellulose to 5-hydroxymethylfurfural. (March 2022) - Liu, Gang; Xie, Yujiao; Wei, Chunjie; Liu, Chang; Song, Feng; Sun, Xiuyu; Zhang, Yuan; Cui, Hongyou
Abstract : The one-pot approach was developed by using molten salt hydrate consisting of ZnCl2 ·4H2 O and LiCl·3H2 O to produce 5-hydroxymethylfurfural (5-HMF) from cellulose. Cellulose was dissolved and regenerated to study the interaction of cellulose and molten salt hydrate. The effects of ZnCl2 ·4H2 O concentration, reaction time, and temperature on the conversion of cellulose to 5-HMF were investigated. 5-HMF yield increased when ZnCl2 ·4H2 O was mixed with LiCl·3H2 O, and the maximum value (44.1%) was reached at 160 °C and 90 min when ZnCl2 ·4H2 O concentration was 64.9 mol%. The species of ZnCl2 ·4H2 O–LiCl·3H2 O were analyzed, and the function of species concentration was correlated with the 5-HMF yield from the conversion of glucose and fructose. It was found that the synergistic catalysis of ZnCl3 −, Zn 2+, Zn(OH) +, H + as well as Li + promoted the efficiently cellulose conversion to 5-HMF. Highlights: Cellulose was efficiently converted to 5-HMF in MSH without additional catalyst. The ZnCl2 ·4H2 O concentration and reaction conditions affected 5-HMF yield. The species of ZnCl2 ·4H2 O–LiCl·3H2 O were calculated and analyzed. The mechanism of synergistic catalysis of species in MSH was proposed.